The effects of ambient particulate matter on human adipose tissue. Issue 9 (3rd May 2019) - Hassan, Lior; Pecht, Tal; Goldstein, Nir; Haim, Yulia; Kloog, Itai; Yarza, Shaked; Sarov, Batia; Novack, Victor
ABSTRACT: The effects of particulate matter (PM) air pollution on adipose tissue have mainly been studied in animal models. The aim of this study was to examine the potential associations between PM exposure and 25 cellular markers in human omental (OM) and subcutaneous (SC) adipose tissue. The PM exposure assessments for both PM2.5 (PM <2.5 μm in diameter) and PM10 (<10 μm) were based upon a novel hybrid satellite-based spatio-temporally resolved model. We calculated the PM exposure above the background threshold for 1 week (acute phase), 3 and 6 months (intermediate phase), and 1 year (chronic phase) prior to tissue harvesting and tested the associations with adipose cell metabolic effects using multiple linear regressions and heat maps strategy. Chemokine levels were found to increase after acute and intermediate exposure duration to PM10 . The levels of stress signaling biomarkers in the SC and OM tissues rose after acute exposure to PM10 and PM2.5 . Macrophage and leucocyte counts were associated with severity of PM exposure in all three duration groups. Adipocyte diameter decreased in all exposure periods. Our results provide evidence for significant contribution of air pollutants exposure to adipose tissue inflammation as well as for pathophysiological mechanisms of metabolic dysregulation that may be involved in the observed responses.